Diabetes Does Not Increase Complications, Length of Stay, or Hospital Costs After Minimally Invasive Transforaminal Lumbar Interbody Fusion. Issue 7 (August 2020) - Narain, Ankur S.; Haws, Brittany E.; Jenkins, Nathaniel W.; Parrish, James M.; Block, Andrew M.; Lamoutte, Eric H.; Karmarkar, Sailee S.; Singh, Kern
Abstract : Study Design: Retrospective cohort. Objective: To determine if the presence of diabetes mellitus as comorbidity is associated with complications, inpatient length of stay, or direct hospital costs after minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Summary of Background Data: Very few studies have investigated the effect of diabetes on complications, length of stay, or costs in minimally invasive lumbar surgeries. Methods: Patients undergoing primary, single-level MIS TLIF were retrospectively reviewed. Diabetic and nondiabetic patients were propensity matched in a 1:1 manner for age, sex, and comorbidity burden. An association between diabetic status and preoperative demographic or perioperative variables, including inpatient length of stay, was tested for using Student t test or χ 2 analysis. Multivariate linear regression was used to test for an association between diabetic status and direct hospital costs. Results: After 1:1 propensity matching, 100 patients were included in this analysis. There were no significant differences in age, sex, body mass index, smoking status, or Charlson Comorbidity Index between propensity-matched patients with and without diabetes. In regards to the length of stay, no significant differences existed between diabetic and nondiabetic groups (68.7 vs. 58.3 h, P =0.218). No other significant differences existed in other perioperative variables including operative time, intraoperative blood loss, or complication rate ( P ≥0.05 for each). Multivariate analysis indicated that diabetic status was not associated with differences in total direct hospital costs (US20, 428 vs. US20, 429, P =0.792) or cost subcategories after MIS TLIF ( P ≥0.05 for each). Conclusions: In this investigation, diabetes was not associated with postoperative complication rates, inpatient length of stay, or direct hospital costs after primary, single-level MIS TLIF. The reduced extent of operative exposure and tissue trauma in MIS TLIF may mitigate the risk of complications in diabetic patients, possibly preventing extensions in hospital stay length and associated hospital costs.